Integration of PRA with GIS for Planning of peri urban areas. - Bandyopadhyay, Piyali (My University, 2018)
Participatory Rural Appraisal (PRA) zielt darauf ab, das Wissen der Bevölkerung des ländlichen Raums in die Entwicklungsplanung des periurbanen Raums einzubeziehen. Im Artikel wird die Kombination von Methoden der Fernerkundung mit PRA erörtert.

Peri-urban areas lack in clarity of planning and development jurisdiction. Its issues are multi facets in nature. The landuse is originally agricultural and arable land is devoted to produce perishable commodities (e.g. vegetables, fruits, flowers and dairy products). With the expansion of urban territory, haphazard and unplanned encroachment of residential and industrial estates takes placed in agricultural and open spaces. The social amenities and public utilities are inadequate and irregularly spaced. This area experiences constant change in land use. The environmental impact of development is not taken into consideration. All these leads to uncontrolled settlement and infrastructure development, lack of interest or attention to retain green areas, arable land, forests, recreational areas, etc. As a consequent of this, there is no forward development planning and control on landuse change. The basic issues of development of Peri urban areas lies in the absence of responsible administrative body for planning and development. Development of peri-urban areas without considering environment aspects, local natural resources and tradition practice leads to chaotic urbanization. The sustainable development of peri urban area needs resource mapping in combination with local traditional practice. The modern technologies like remote sensing and geographical information system (GIS) allow us to collect physical data rather easily with speed and on repetitive basis, GIS helps to analyze the data spatially with various options of modeling and other planning processes. Participatory Rural Appraisal (PRA) aims to incorporate the knowledge and opinions of rural people in the planning and management of development projects and programmes, The integration of PRA with GIS will help the planners to prepare the plan where both traditional knowledge and modern technology are used to prepare development plan. In this paper attempts are made to understand the characteristics and issues associated with peri-urban areas and how both traditional and modern techniques can be used to prepare sustainable development plan for Peri-urban areas.
Keywords: Stadtumland; Randzone; Ländlicher Raum; Stadt-Land-Beziehung; Verstädterung; Stadtwachstum; Stadtentwicklungsplanung; Partizipation; Bewohnerbeteiligung; Fernerkundung; GIS; Planungsmethode